ASCO 2007: "Translating Research into Practice". Report from the 34th Annual Meeting of the American Society of Clinical Oncology - Camillo Porta (Frontiers Media S.A., 2011)
This year, for the 34th time in its history, the mastodontic machinery of the American Society of Clinical Oncology (ASCO) once again welcomed thousand of members and participants from all over the world to the Society's annual meeting, which, this year, took place in the ample and well-appointed, McCormick's Convention Center in Chicago, Illinois...